2023
DOI: 10.1002/jor.25647
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for ex vivo mechanical testing of tendon

Abstract: Tendons are critical for the biomechanical function of joints. Tendons connect muscles to bones and allow for the transmission of muscle forces to facilitate joint motion. Therefore, characterizing the tensile mechanical properties of tendons is important for the assessment of functional tendon health and efficacy of treatments for acute and chronic injuries. In this guidelines paper, we review methodological considerations, testing protocols, and key outcome measures for mechanical testing of tendons. The goa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 81 publications
0
2
0
Order By: Relevance
“…However, the compression test of tendon after enzyme treatment was not found. It may be because tendons are more influenced by uniaxial direction (that is, fiber direction) in vivo , and axial tension is a conventional mechanical test method ( Ristaniemi et al, 2021 ; Lake et al, 2023 ). Through uniaxial stretching, it is concluded that elastin has made a more significant contribution to the patellar tendon as an energy storage tendon.…”
Section: Discussionmentioning
confidence: 99%
“…However, the compression test of tendon after enzyme treatment was not found. It may be because tendons are more influenced by uniaxial direction (that is, fiber direction) in vivo , and axial tension is a conventional mechanical test method ( Ristaniemi et al, 2021 ; Lake et al, 2023 ). Through uniaxial stretching, it is concluded that elastin has made a more significant contribution to the patellar tendon as an energy storage tendon.…”
Section: Discussionmentioning
confidence: 99%
“…Also, clamping could impose a strong compression force not represented by the constitutive law which is only valid in the tensile state and at low dispersion. As such, experimentally, clamping modifications (e.g., sinusoidal-shaped or serrated jaws, sandpaper) are employed to increase the contact area of the clamp across the sample ( Lake et al, 2023 ). Furthermore, incompressibility as a characteristic of soft tissues in computational biomechanics is not valid if the sample becomes dehydrated during an experiment.…”
Section: Discussionmentioning
confidence: 99%